Desempenho de escolares com dislexia e transtorno do déficit de atenção e hiperatividade nos processos de leitura - Oliveira, Adriana Marques de [UNESP] (2011)
This study aimed to characterize and to compare the performance of students with an interdisciplinary diagnosis of dyslexia and attention deficit hyperactivity disorder (ADHD) in students with good academic performance on the reading processes. Sixty students from both genders, from 2nd to 4th grades of municipal public schools in Marília - SP participated in this study, they were distributed as follows: GI, 20 students with interdisciplinary diagnosis of dyslexia; GII, 20 students with ADHD and GIII, 20 students with good academic performance, paired according to gender, age and grade level with GI and GII. The students were submitted to the application of the assessment of reading processes (PROLEC) composed by four processes: letters identification, lexical, syntactical and semantic. The results highlighted that the students of GIII showed superior performance comparing with GI and GII. There was difference between GI and GII only in low frequency word reading and non words reading of the lexical process. The inferior performance from GI and GII in the PROLEC tests can be justified by the difficulty on the coding and decoding abilities. In ADHD students this difficulty was due to impaired interaction between the visual, linguistic, attention and auditory processing and in the dyslexic students was due to failure at the phonological mediation process, which depends on the knowledge of rules of grapheme - phoneme conversion to the acquisition of word reading. These changes affect the reading achievement and the comprehension of the read text.